CONIELECOMP 2011, 21st International Conference on Electrical Communications and Computers 2011
DOI: 10.1109/conielecomp.2011.5749365
|View full text |Cite
|
Sign up to set email alerts
|

Margin adaptive resource allocation for multiuser OFDM systems by modified Particle Swarm Optimization and Differential Evolution

Abstract: Like many wireless systems, Orthogonal Frequency Division Multiplexing (OFDM) needs proper allocation of limited resources such as total transmit power and available frequency bandwidth among the users to meet their service requirements. In this paper, different versions of two evolutionary approaches, Differential Evolution (DE) and Particle Swarm Optimization (PSO) have been applied for adaptive sub-carrier and bit allocations to minimize the overall transmit power of a multiuser OFDM system. Each user will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Solution to the adaptive resource allocation in OFDMA has been broadly divided into two categories: margin adaptive and rate adaptive (RA) . Some typical margin adaptive schemes have been developed to find the solution minimizing the overall transmit power, given constraint on the users' data rates, or bit error rate (BER) .In this paper, RA is considered. The aim of RA is to maximize the minimum data rate of users subject to power constraint .…”
Section: Introductionmentioning
confidence: 99%
“…Solution to the adaptive resource allocation in OFDMA has been broadly divided into two categories: margin adaptive and rate adaptive (RA) . Some typical margin adaptive schemes have been developed to find the solution minimizing the overall transmit power, given constraint on the users' data rates, or bit error rate (BER) .In this paper, RA is considered. The aim of RA is to maximize the minimum data rate of users subject to power constraint .…”
Section: Introductionmentioning
confidence: 99%
“…In [11] PSO was applied for sub-channel allocation in downlink OFDMA and provided better sum-capacity values. Ahmed [12] has shown that the Differential Evolution techniques is better than PSO but takes more time to converge. The Bees algorithm has not yet applied for the problem of resource allocation.…”
Section: Related Workmentioning
confidence: 99%
“…GAs were shown to outperform other conventional iterative methods in these results. There are a few reports in the literature where EAs other than GAs were used for resource allocation .…”
Section: Related Workmentioning
confidence: 99%
“…This approach allows efficient use of all the subcarriers. Resource allocation in OFDMA includes subcarrier allocation, power allocation and bit loading. Developing efficient resource management techniques for such a set‐up has drawn enormous attention in recent years.…”
Section: Introductionmentioning
confidence: 99%